Meningkatkan Aktivitas, Berpikir Kritis, dan Hasil Belajar Menggunakan Model PENA Pada Muatan Pendidikan Pancasila Di Sekolah Dasar - Suhaimi; Nurleny Amawaddah (CV. ITTC INDONESIA, 2024)
This research identifies problems regarding low activity, critical thinking, and student learning outcomes in the learning process. To overcome this problem, the effort made is to apply the PENA model in classroom learning activities. This research aims to describe teacher activities, analyze student activities, analyze critical thinking skills and student learning outcomes. This research used Classroom Action Research (PTK), carried out in 4 meetings in class IV of SDN Belitung Selatan 9 with a total of 9 students consisting of 5 male students and 4 female students in semester 2 of the 2023/2024 academic year. Research findings show that teacher activity has increased, as evidenced by a score of 36 which has a very good criteria value. Student activity with very active criteria reaches 100%. Critical thinking ability increased by up to 89%. And, with the criteria achieved, student learning outcomes increase by 100%. Thus it can be concluded that the use of the PENA learning model can increase teacher activity, student activity, critical thinking skills and learning outcomes. The results of this research can be used as an alternative for choosing and using learning models, especially Pancasila education content.